The Nutritional Status of Breastfeeding Mothers and Breastfeeding Adequacy in Indonesia: A Systematic Review - Rachmadiani, Ainindya Pasca; Nadhiroh, Siti Rahayu (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: One of the basic capitals for the formation of quality human beings is the consumption of breast milk. The amount of breast milk produced is highly dependent on the mother's diet. This study aimed to identify the relationship between the nutritional status of breastfeeding mothers and breast milk adequacy in Indonesia. Subjects and Method: This was a systematic review using PICO model to formulate the research question. Population= breastfeeding mothers. Intervention= adequate BMI and MUAC. Comparation= poor BMI and MUAC. Outcome= breast milk adequacy. The database used is Google Scholar with keywords “Anthropometry” OR “BMI” OR “Breastfeeding mothers” OR “breast milk adequacy” OR “Indonesia”. There were 10 cross-sectional studies and 2 cohort studies published in 2011-2023 that met the inclusion criteria. Results: There is mostly a relationship between the nutritional status of breastfeeding mothers as measured by BMI and MUAC with the adequacy of breast milk. Conclusion: The adequacy of breast milk can be influenced by the nutritional status of the mother while breastfeeding. The nutritional status of breastfeeding mothers is no less important than the nutritional status of pregnant women so that risks such as stunting do not occur.